2021
DOI: 10.1038/s41598-021-81638-1
|View full text |Cite
|
Sign up to set email alerts
|

Altered high-density lipoprotein composition and functions during severe COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) pandemic is affecting millions of patients worldwide. The consequences of initial exposure to SARS-CoV-2 go beyond pulmonary damage, with a particular impact on lipid metabolism. Decreased levels in HDL-C were reported in COVID-19 patients. Since HDL particles display antioxidant, anti-inflammatory and potential anti-infectious properties, we aimed at characterizing HDL proteome and functionality during COVID-19 relative to healthy subjects. HDLs were isolated from plasma of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
88
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 55 publications
12
88
0
3
Order By: Relevance
“…One study showed that HDLs from COVID-19 patients were less protective for endothelial cells stimulated with TNFα than HDLs from healthy subjects. 13 The proteins identified may be potential indicators of a prolonged cholesterol metabolism disorder. From the clinical data obtained from patient blood samples ( Figure 1 a), we found that the serum total cholesterol level and the low-density lipoprotein level were increased at disease onset and did not fully return to the original values even at the 6 month follow-up, both in moderate and severe COVID-19 patients ( Figure 3 e and Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study showed that HDLs from COVID-19 patients were less protective for endothelial cells stimulated with TNFα than HDLs from healthy subjects. 13 The proteins identified may be potential indicators of a prolonged cholesterol metabolism disorder. From the clinical data obtained from patient blood samples ( Figure 1 a), we found that the serum total cholesterol level and the low-density lipoprotein level were increased at disease onset and did not fully return to the original values even at the 6 month follow-up, both in moderate and severe COVID-19 patients ( Figure 3 e and Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…PON1 activity in the serum of COVID-19 patients may be lower for several, though not mutually exclusive, reasons. SARS-CoV-2 infected patients are known to often have low HDL levels [ 27 ], and recent studies reported that patients with severe COVID-19 had lower HDL cholesterol and higher triglyceride levels before and after the infection than patients without severe COVID-19 or the healthy population [ 28 , 29 ]. Begue et al [ 29 ] found that the HDL cholesterol concentration of COVID-19 patients admitted to the Intensive Care Unit was about half that of healthy individuals and that their HDL particles were enriched in various inflammatory proteins and depleted in PON1.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, reverse cholesterol transport mediated by ATP-binding cassette transporter (ABC) and lecithin-cholesterol acyltransferase (LCAT) are decreased during inflammation, leading to decreased HDL (30). Lower serum lipid levels are also associated with greater levels of systemic inflammation in other infections (9)(10)(11)(31)(32)(33). A similar clinical scenario has been explored in patients with rheumatoid arthritis (RA).…”
Section: Discussionmentioning
confidence: 99%